Experimental investigation of the influence of blending on engine emissions of the diesel engine fueled by mahua biodiesel oil. Issue 8 (18th April 2018) - Kumar, Sunil; Kumar, Sachin; Kumar, Abhishek; Maurya, Sachin; Deswal, Vikas
ABSTRACT: The present article elaborates on the various emission characteristics of mahua oil with diesel fuel in a diesel engine at various blending conditions. Experimental investigation results are studied for various parameters such as exhaust emission of carbon monoxide (CO), hydrocarbon (HC), and oxides of nitrogen (NO) gases and exhaust gas temperature. Results show that residual oxygen, CO, HC, and NO emission were the lowest for mahua biodiesel compared with diesel. The experimental results proved that the use of mahua oil biodiesel as fuel in the diesel engine is a viable alternative to diesel fuel. Mahua biodiesel oil may be beneficial in decreasing greenhouse gas emissions without any engine modification. Mahua oil has the possibility of becoming a sustainable fuel source as biodiesel.